Effect of nano-silica addition into high volume fly ash–hydrated lime blended concrete. (30th August 2020) - Gunasekara, Chamila; Sandanayake, Malindu; Zhou, Zhiyuan; Law, David W.; Setunge, Sujeeva
Highlights: Two HVFA concrete mixes utilizing 65% and 80% cement replacement, were developed. Nano-silica & Hydrated lime increased early age hydration involving C3 A and C4 AF phases. Formation of Monosulfoaluminate contribute to early age compressive strength gain. HVFA concrete displayed 51–60% carbon savings and a reduced Global Warming Impact. HVFA concrete shows a 10% cost reduction compared with Portland Cement concrete. Abstract: This study investigates strength development, reactivity and environmental/economic benefits of blended High Volume Fly Ash (HVFA) concrete mixes utilizing 65% and 80% cement replacement utilizing a combination of fly ash and hydrated lime, with and without nano-silica. The carbon and non-carbon emissions are considered as environmental impacts while life cycle costs from cradle-to-gate, which is from material extraction to production, are considered for comparison of the economic benefits. The compressive strength of the HVFA mixes increased with the addition of nano-silica. The HVFA–65 and HVFA–80, without nano-silica, achieved 25.0 MPa and 14.5 MPa at 7 days, respectively, and 42.7 MPa and 29.5 MPa at 28 days. With the addition of nano-silica the HVFA–65 ns and HVFA–80 ns concrete had compressive strengths of 37.5 MPa and 28.8 MPa at 7 days and increased to 47.1 MPa and 40.1 MPa at 28 days. Incorporating 3% nano-silica into HVFA concrete increased the early age hydration reaction. This is attributed to the reaction of the C3 A and C4 AF phases and the formation of monosulfoaluminate, which contributed to the early age strength gain. The majority of Ca 2+ ions were consumed during the initial hydration, with few Ca 2+ ions remaining for the subsequent hydration reaction with the C3 S phase. The HVFA concrete mixes displayed between 51 and 60 % carbon savings and a reduced Global Warming Impact. The non-Greenhouse Gas emissions, i.e. SO2 and NOx, reflects minor savings in the Acidification Impact (AI) and Photochemical Oxidant Formation Impact (POFI) environmental impact indicators. Further, HVFA concrete incorporated with hydrated lime shows a 10% cost reduction compared with Portland Cement concrete.